Investigation of Sodium Manganese Oxide Nanowires Synthesized by Hydrothermal Method for Alkaline Ion Battery - Tan, Ta Anh; Phuong, Do Thi; Oanh, Nguyen Thi Tu; Mai, Do Xuan; Chung, Hoang Vu; Chi, Le Ha; Chien, Dang Tran; Long, Pham Duy (Communications in Physics, 2014)
Sodium Manganese Oxide (NaxMnO2) has attracted much attention as cathode materials for alkaline ion battery due to the ability of fast charge and discharge ion Na+, in particular in nanoscale. We report on the synthesis of NaxMnO2 nanowires via hydrothermal synthesis route from Mn2O3 and NaOH solution. The morphological observation indicates that the obtained Na0.44MnO2 nanowires with diameters of about 20-30 nm, length up to several micrometers were formed by this process. The electrochemical properties of fabricated materials were investigated by means of cyclic voltammetry technique and show that Sodium Manganese Oxide (NaxMnO2) is a promising material in the field of research and fabrication alkaline ion battery.